Pengaruh Terapi Aktivitas Kelompok Terhadap Penurunan Frekuensi Halusinasi Pasien Skizofrenia - Mardiana, Nova; Nurwijaya Fitri; Ardiansyah (Institut Citra Internasional, 2025)
Mental disorders are still a hot and serious topic of discussion globally. The number of people suffering from mental disorders increases every year in various parts of the world. One form of mental disorder is schizophrenia. The purpose of this study was to determine the effect of group activity therapy on reducing the frequency of hallucinations in schizophrenia patients. This study is a quantitative study with a quasi experiment using a one group pre-test post-test approach. The sample in this study was 19 patients who were taken through a purposive sampling technique. Data collection was carried out using a questionnaire observation sheet and using the T-test. The results of the study showed that the average score of the frequency of hallucinations before being given group activity therapy was 6.42, while after being given group activity therapy the average score was 5.37. Then from the results of the statistical data analysis showed a p-value of 0.000 <0.05 (?) which means there is a significant difference in the average score before and after being given group activity therapy on reducing the frequency of hallucinations in schizophrenia patients at the dr. Mental Hospital. Samsi Jacobalis Bangka Belitung Islands Province in 2023. The conclusion of this study is that there is an effect of group activity therapy on reducing the frequency of hallucinations in schizophrenia patients. The researcher's suggestion for the form of group activity therapy can be modified according to the situation and conditions at the Hospital.